STRATEGI PENGEMBANGAN UMKM BERBASIS INOVASI & PLATFORM DIGITAL - Aditiya, Variza; Lastri, Novelma; Hartutik, Dwi; Musdiana, Andi Desy; Mustafa, Said (Smart Education, 2026)
Abstract: This study aims to synthesize findings from three recent studies discussing the development strategies of Small and Medium Enterprises (SMEs) through digital innovation, collaborative governance, and technological transformation. The analyzed studies include innovation-based SME development strategies, collaborative ecosystem approaches involving government and business actors, and digital transformation frameworks to enhance competitiveness. Using a qualitative literature synthesis method, this study examines key themes, methodologies, and outcomes across the selected research. The results indicate that digital transformation serves as a primary driver for SME competitiveness, while collaborative governance enhances institutional support and ecosystem resilience. Innovation capability, access to digital platforms, and stakeholder collaboration emerge as critical success factors. The synthesis also highlights that SMEs require not only technological adoption but also capacity building, policy alignment, and adaptive business strategies. This study contributes to the growing discourse on SME development by integrating technological, institutional, and strategic perspectives into a unified analytical framework. Keywords: SMEs Development, Digital Transformation, Collaborative Governance, Innovation Strategy. Abstrak: Penelitian ini bertujuan untuk mensintesis temuan dari tiga studi terbaru yang membahas strategi pengembangan Usaha Mikro Kecil dan Menengah (UMKM) melalui inovasi digital, tata kelola kolaboratif, dan transformasi teknologi. Studi yang dianalisis meliputi strategi pengembangan UMKM berbasis inovasi, model kolaborasi antara pemerintah dan pelaku usaha, serta kerangka transformasi digital untuk meningkatkan daya saing. Menggunakan metode sintesis literatur kualitatif, penelitian ini mengkaji tema utama, metodologi, dan hasil dari penelitian yang dipilih. Hasil menunjukkan bahwa transformasi digital menjadi faktor utama dalam meningkatkan daya saing UMKM, sementara tata kelola kolaboratif memperkuat dukungan kelembagaan dan ketahanan ekosistem usaha. Kapabilitas inovasi, akses platform digital, dan kolaborasi pemangku kepentingan menjadi faktor kunci keberhasilan. Studi ini berkontribusi dalam memperkaya diskursus pengembangan UMKM melalui integrasi perspektif teknologi, institusional, dan strategis. Kata Kunci: Pengembangan UKM, Transformasi Digital, Kolaborasi Tatakelola, Strategi Inovasi.